Comparison of intracerebral and systemic haemodynamics in severe traumatic brain injured patients receiving dexmedetomidine or propofol as sedative agents - Kadir, Wan Daud Wan (2010)
Sedation in neurosurgical intensive care unit is crucial as it does not merely overcome anxiety and facilitate ventilation but may prevent deleterious changes in intracranial pressure and cerebral perfusion pressure. The aim of this study is to explore the efficacy of dexmedetomidine compared to propofol for sedation in severe traumatic brain injured patients. This study will focus on the effects of dexmedetomidine compared to propofol on the cardiovascular haemodynamics, cerebral haemodynamics and sedation on severe traumatic brain injured patients. A prospective and randomized trial was conducted on post craniectomy patients with severe traumatic brain injury and who were ventilated in neurosurgical intensive care unit. Thirty patients were randomized to receive either dexmedetomidine (n=l5) or propofol (n= 15). The infusion rate was titrated to achieve bispectral index (BIS) of 60 to 70. Cardivascular and cerebral haemodynamics, analgesic requirement and extubation time were measured and compared. Demographic data were comparable in both groups. Titration of sedation in both groups was able to achieve the same mean of SAS score and BIS score. There were no significant differences in mean BP, MAP, ICP and CPP between dexmedetomidine and propofol. Heart rates were found to be significantly low in dexmedetomidine group (58.08 per min CI:51.54,64.62) and propofol (77.06 per min; CI:70.52,83.60) with p<O.Ol. The analgesic requirement were marginally lower in dexmedetomidine compared to propofol (p=0.06). There were no differences in terms of extubation time between the two groups. This study showed that dexmedetomidine was comparable to propofol in the provision of sedation in post craniectomy in severe traumatic brain injured patients. Dexmedetomidine was comparable in terms of cardiovascular and intracerebral haemodynamics except patient treated with dexmedetomidine has lower heart rates. There was also reduction in the needs for additional analgesia with dexmedetomidine even though it was not statistically significant.